Drug interactions in prescriptions for patients with conditional anticoagulation in two specialized outpatient clinics (Research, Society and Development, 2024)
Objective: to identify medication prescriptions for elderly patients undergoing anticoagulant treatment and potential interactions with warfarin. Methodology: Descriptive study, with patients with atrial fibrillation, over 18 years of age, treated at the anticoagulation outpatient clinics of two hospitals in Belo Horizonte, between June and December 2018, using warfarin for at least six months. Patients at these outpatient clinics were approached to identify medication prescriptions made by primary care doctors. The variables were analyzed: medications used and potential drug interactions with warfarin, observing the frequencies through the database created in an Excel spreadsheet. Results: at Hospital 1, 127 patients were evaluated, with a median age of 66 years, the majority of whom were men (50.4%). The most commonly used medications were: simvastatin (21.3%), spironolactone (14.6%) and omeprazole (11.9%). Of the total number of patients, 106 use medications that can interact with warfarin. At Hospital 2, 105 patients were evaluated, with a median age of 65 years, the majority of whom were women (67.6%). The most prescribed medications were: simvastatin (19.6%), omeprazole (15.8%) and acetylsalicylic acid (14.2%). At this institution, 99 patients used medications that could interact with warfarin. Conclusion: there is a high frequency of prescription of medications that interact with warfarin in the populations studied, reinforcing the need for therapeutic monitoring.